Association between pulmonologists' tobacco use and their effort in promoting smoking cessation in Turkey: a cross-sectional study. Issue 1 (December 2015) - Pazarli Bostan, Pinar; Karaman Demir, Canan; Elbek, Osman; Akçay, Şule
Abstract Background A strategy to reduce the number of smoking-related deaths is to encourage the involvement of health-care professionals in tobacco-use prevention activities and cessation counseling. Previous studies have shown that physicians' smoking status affects their efforts to provide smoking cessation counseling. This study investigates the association between pulmonologists' tobacco use and their efforts in promoting smoking cessation during their routine clinical practices in Turkey. Methods This cross-sectional study was performed among active members of the Turkish Thoracic Society (TTS) between June 2010 and February 2011 using an Internet-based self-administered questionnaire. Participants gave their written informed consent. The survey included questions about responders' sociodemographics, smoking status, and their routine clinical practice for smoking cessation counseling using the basic 5A's (Ask, Advise, Assess, Assist, and Arrange) of smoking cessation counseling. According to the total score for the 5A's protocol, smoking cessation counseling was dichotomized into low- and high-effort groups in promoting smoking cessation. Pearson's chi-square test andt -test were used to compare groups and logistic regression models for the research question, which was approved by the TTS Scientific Ethical Committee. Results The response rate was 41 % (N = 699/1701); 9.9 % were current smokers, and 72.7 % indicated that they provided high effort in promoting smoking cessation. A univariate analysis showed that noncurrent smokers were more likely to make a high effort than current smokers (odds ratio [OR], 1.82; 95 % confidence interval [CI]: 1.09–3.05;P = 0.02). However, there was no association between tobacco use (current smoking) and making high effort in promoting smoking cessation after controlling for the two confounders, sex and practicing in smoking cessation outpatient clinic (OR, 1.47; 95 % CI: 0.86–2.50;P = 0.1). Conclusions Despite low response rate in our study and suspicions of underreporting, the smoking rate among the pulmonologists in our study was high. Non-current smokers were more likely to provide high effort in promoting smoking cessation compared to current smokers in univariate analysis. However, after controlling for the two confounders, sex and practising in SCOC, there was no association between tobacco use and providing high effort in promoting smoking cessation. Thus, improving medical school education, specialty training and post-graduate training on smoking cessation counseling may positively affect physician' effort in promoting smoking cessation.